Somatic embryogenesis and plant regeneration from transverse thin cell layers of adult peach palm (Bactris gasipaes) lateral offshoots - Campos-Boza, Stefanny; Vinas, María; Solórzano-Cascante, Paul; Holst, Andrea; Steinmacher, Douglas A.; Guerra, Miguel P.; Jiménez, Víctor M. (Frontiers in Plant Science, 2022)
In this work we report a successful protocol to obtain in vitro peach palm (Bactris gasipaes Kunth) “Diamantes 10” plants through somatic embryogenesis from thin cell layer (TCL) explants, dissected from three sections (basal, medial and apical) of lateral offshoots of adult plants cultured on different concentrations of 4-amino-3,5,6-trichloropicolonic acid (picloram). After swelling and development of primary callus in all treatments, without any strong effect of explant origin or picloram concentration, it was possible to observe the formation of embryogenic structures and the exact point from where they developed. Browning was also observed and correlated to the induction treatments, although it was not an impairment for the production of embryogenic structures. Subsequent maturation and conversion of somatic embryos into plantlets allowed their acclimatization 17 months after culture initiation, which was quicker than previous reports with juvenile tissues (from embryos or seed germinated plantlets). To the best of our knowledge, this is the first report on peach palm regeneration by means of somatic embryogenesis from TCL explants from adult plants and could constitute, after fine-tuning the acclimatization stage, a tool for mass clonal propagation of elite genotypes of this open-pollinated crop, as well as for the establishment of conservation strategies of in situ gene bank plant accessions endangered due to ageing and other threats.